(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aimed at figuring out and knowing the views of the community towards the Gantarangkeke traditional party and how the Gantarangkeke effects are towards the community behavior patterns. The qualitative research type was used and the researcher used descriptive analysis. The data collected was in the form of words and pictures. While making observations, the researcher participated in doing what the data sources did. The type of interview that the researcher used was a structured interview. This was used in order to obtain information or data about people’s lives of Gantarangkeke who are adhered to ancestral beliefs. The things that were asked of the informants included, among other things, the meaning of Gantarangkeke, the origin of the emergence of the Gantarangkeke belief, the influence of the Gantarangkeke belief on people who still maintain traditions, forms of ritual, and the understanding of people who still carry out ancestral beliefs. The result of this research showed that from the information obtained, the origin of the Gantarangkeke belief arises because of the story about Tumanurung who descended on Gantarangkeke at that time to take care of the world and the hereafter. It was considered to have an influence in its daily life, especially when Tumanurung was in Gantarangkeke at that time he was considered to have extraordinary powers. Traditions or ancestral culture in the life of the Gantarangkeke community which is still ongoing today has an influence on the life of the Gantarangkeke community. Meanwhile, in the social aspect, there are changes that occur both in terms of community culture, development and economy. The Gantarangkeke belief, in conclusion, still had a great influence until now on most people from various parts of the region, especially the people of the Gantarangkeke area.